2018
DOI: 10.1016/j.atmosenv.2017.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the uncertainty in emissions over India with a regional air quality model evaluation

Abstract: To evaluate uncertainty in the spatial distribution of air emissions over India, we compare satellite and surface observations with simulations from the U.S. Environmental Protection Agency (EPA) Community Multi-Scale Air Quality (CMAQ) model. Seasonally representative simulations were completed for January, April, July, and October 2010 at 36km x 36km using anthropogenic emissions from the Greenhouse Gas-Air Pollution Interaction and Synergies (GAINS) model following version 5a of the Evaluating the Climate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…In addition estimating rural emissions by extrapolation from urban data can be problematic. Karambelas et al (2018) found large low biases across modeled concentrations evaluated with satellite and surface observations, demonstrating the importance of having representative inventories and high-resolution chemical transport models. Emissions inventories are invaluable to air quality modeling and for estimating human health impacts due to pollution exposure, playing a vital role in advancing air quality and health understanding in India.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…In addition estimating rural emissions by extrapolation from urban data can be problematic. Karambelas et al (2018) found large low biases across modeled concentrations evaluated with satellite and surface observations, demonstrating the importance of having representative inventories and high-resolution chemical transport models. Emissions inventories are invaluable to air quality modeling and for estimating human health impacts due to pollution exposure, playing a vital role in advancing air quality and health understanding in India.…”
Section: Introductionmentioning
confidence: 94%
“…Air quality modeling was performed using the regional CMAQ model version 5.1. Previously, CMAQ has been used in India to assess O 3 regimes (Sharma et al 2016, Sharma andKhare 2017) and evaluate urban and rural emissions uncertainties (Karambelas et al 2018). We completed simulations for four seasonally representative months using 2010 meteorology and emissions: January, April, July, and October for winter, pre-monsoon spring, monsoon, and postmonsoon fall respectively.…”
Section: Modelingmentioning
confidence: 99%
See 3 more Smart Citations